Regional Head Election post-MK Decision Number 60/PUU-XXII/2024 in the constitutional law landscape - Hufron Hufron; Sultoni Fikri; Syofyan Hadi; Baharuddin Riqiey (Legality : Jurnal Ilmiah Hukum, 2025)
This article aims to analyse the implications of the Constitutional Court's decision on the regional head election system in Indonesia and evaluate its impact on political participation and diversity within local democracy. The Constitutional Court, as the interpreter of the constitution, particularly in the context of regional head elections, plays a pivotal role in shaping the landscape of constitutional law. Constitutional Court Decision No. 60/PUU-XXII/2024, which controversially alters the candidacy requirements for regional heads from being based on seat or vote share to being based on population size, reflects the need to align the law with evolving socio-political dynamics. This legal research employs statutory, conceptual, and case study approaches. This decision is expected to broaden access for smaller parties and independent candidates, thereby enhancing political diversity and voter choice. However, there is a risk that the changes might induce political instability or lead to dominance by large parties. Thus, ongoing monitoring and evaluation of the impact of these changes are crucial to ensure that constitutional law reforms achieve their intended goals of justice and representation. This article contributes to understanding how the law can adapt to societal needs and the challenges faced in the democratisation process. By emphasising the importance of legal pragmatism, the article illustrates that the law should function as a theoretical norm and an effective tool for addressing the continuously evolving socio-political dynamics. The research is intended to serve as a reference for policymakers and academics in comprehending and implementing constitutional law reform in Indonesia.